Risk Assesment Pengelolaan Limbah Padat Medis Rumah Sakit Umum Daerah Gambiran Kota Kediri - Doutti Shoshihandra; Abdul Rohim Tualeka (Media Gizi Kesmas, 2023)
Background: Hospital waste is waste generated from hospital activities and other supporting activities that could have an impact on public health and the surrounding environment.  Problems that occurs due to medical solid waste which oftenly unseparated resulting in the occurrence of occupational disease and work-related accidents. Objectives: The aim of this research is targeting the implementation of risk assessment of medical solid waste management at Gambiran Public Hospital, Kediri City. Methods: This study is a descriptive study with quantitative methods applying cross sectional design.  The study was held at Gambiran Public Hospital on July 4th - August 5th 2022. Results: This results showed that the dangers of the medical solid waste management process at Gambiran Public Hospital, Kediri City, originate from collecting activities, sorting medical solid waste towards waste transportation, including needle punctured, contact with infectious materials and chemicals, inappropriate work postures such bending, squatting, lifting excess weight, as well as performing repetitive work. Other sources of threat arise from environment or construction including uneven pathways and slippery floors Conclusions: Based on the result of the medical solid waste management risk assessment, Gambiran Public hospital, Kediri City has a high risk of low back pain, back pain, hand pain, as well as being infected with infectious disease as an outcome of needle punctured accident.